Biomass use and its health effects among the vulnerable and marginalized refugee families in the Gaza Strip - Elbayoumi, Maher; Albelbeisi, Ahmed Hassan (Frontiers in Public Health, 2023)
Introduction Biomass fuel remains the most common type of fuel used in many developing countries, leading to indoor air pollution and serious health impacts. Objective The objective of this study was to compile evidence on the impact household fuel combustion has on child and adult health, with an emphasis on solid fuel use in Gaza. Methods In this cross-sectional study, 110 structured self-administered questionnaires were distributed in April 2019 among families living in the Al-Maghazi refugee camp. Results Participants reported that the main fuel used were wood, coal, cardboard, and a mix of wood, cardboard, and plastic, which were used for cooking, heating, baking, boiling water, and lighting. The most common symptoms were nasal irritation (71.8%), followed by headache (66.4%) and dizziness (65.4%). The results of logistic regression showed that the participants who used wood fuel had a higher chance of feeling eye irritation than those who used a mix of wood, cardboard, and dried grass (OR = 1.316; 95% CI = 1.54–8.99). The participants who opened windows during the burning process of biomass fuel were five times more likely to develop pneumonia than those who closed windows (OR = 5.53; 95%CI = 11.60–19.0). Conclusion there is an urgent need for community awareness campaigns designed to inform people about the risks of exposure to biomass fuel smoke and how to better implement household ventilation.